If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y in (-oo:+oo)
(3/5)*y-4 = 2 // - 2
(3/5)*y-4-2 = 0
3/5*y-6 = 0 // + 6
3/5*y = 6 // : 3/5
y = 6/3/5
y = 10
y = 10
| 12(3-2x)=84 | | -2x+2=-5x+29 | | 78=6.5z | | 7w=24+w | | 6log(4x)=18 | | 9(4g-3)= | | d/-73 | | -2x-2=5+5x | | 11(n+3)+3=3 | | 7/8*3 | | 5x+5r-2x+r= | | -2x+10=-5x+10 | | 3k+4=7 | | 4(2g-5)= | | 4/9*2 | | 0x=-7y | | -5.5X^2+198=0 | | -2.8=a+3.1 | | -6p+48=12 | | 10+5x=-5x+60 | | Ln(5x+4)=ln(3-x) | | 6x-3(2x+5)=8 | | 4st+3-2ts+6s= | | 5n+8=53 | | 5-3x=2x+45 | | t(f)=16f^2+32f | | t(f)=16f^2+32t | | K^2-12k-4=2 | | 6x+8=0-2x | | 4a=5b | | -16=-0.2k | | 7*(3x-6)-15=110-4(17-x)-5x |